Pseudomonads contribute to regulation of Pratylenchus penetrans (Nematoda) populations on apple - Watson, Tristan T; Forge, Tom A; Nelson, Louise M (Canadian journal of microbiology, 2018)
Inoculation with antagonistic soil microorganisms has shown potential to suppress replant disease of apple in orchard soils. Pseudomonas spp. may have the potential to reduce Pratylenchus penetrans populations on apple. Pseudomonas spp. were isolated from the rhizosphere of sweet cherry and screened for antagonistic characteristics. Two highly antagonistic Pseudomonas isolates, P10-32 and P10-42, were evaluated for growth promotion of apple seedlings, suppression of P. penetrans populations, and root colonization in soil from three orchards. During the isolate screening, Pseudomonas fluorescens P10-32 reduced in vitro growth of fungal pathogens, had protease activity, had capacity to produce pyrrolnitrin, suppressed P. penetrans populations, and increased plant biomass. Pseudomonas fluorescens P10-42 reduced in vitro growth of fungal pathogens, had protease activity, suppressed P. penetrans populations, and increased plant biomass. In potted orchard soil, inoculating apple with P. fluorescens P10-32 suppressed P. penetrans populations in one of the three soils examined. Inoculation with P. fluorescens P10-42 improved plant growth in two of the soils and suppressed P. penetrans abundance in one soil. In one of the soils, P. fluorescens P10-42 was detected on the roots 56 days postinoculation. Overall, we conclude that Pseudomonas spp. play a role in suppressing P. penetrans on apple in orchard soil.